Integrating intercultural competence in FL classroom: Strategies and perspectives of educators - Narke, Pankaj (Journal of International Students, 2026)
In recent years, there has been an increasing demand to make students interculturally competent, preparing them to become global citizens. Individuals must have relevant intercultural and communicative competencies to function effectively in multicultural and multilingual environments. One common way to enhance intercultural competence (IC) is through teaching a foreign language (FL).  FL teachers promote the acquisition of intercultural competence through a range of teaching materials and techniques; however, there is insufficient research documenting their experiences. This paper explores teachers’ beliefs and practices regarding the integration of intercultural communicative competence (ICC) among adult FL learners. 60 FL instructors from 17 countries, who taught 16 FLs at 29 universities and colleges across the USA, participated in this study. Data were collected through a questionnaire and semi-structured interviews with educators, which were analyzed using a mixed-methods approach. The Likert-scale items were analyzed using descriptive statistics, and the open-ended responses were analyzed using thematic analysis. Byram’s (2020) ICC framework was applied for analyzing the data, suggesting that educators explore all the ICC dimensions, including knowledge, discovery skills, interaction skills, interpreting and relating skills, and critical cultural awareness, to simulate conditions that encourage learners to practice communicating in multilingual and multicultural settings.  Respondents reported that learners’ knowledge of the FL culture plays a significant role in their success in learning the target language. They also observed that the use of intercultural input enhanced FL learners’ pragmatic understanding, vocabulary, and speech production. Consequently, they frequently use cultural themes in instructional materials and assessments, which they believe have helped develop learners' overall FL skills.